Physical Characteristics And Phytochemical Screeningfrom Oil And Red Fruit Juice (Pandanus Conoideus L.) - Aulia, Wasilatul; Febriyanti, Rizki; Amananti, Wilda (Indonesian Journal of Chemical Science and Technology (IJCST), 2024)
Red Fruit Oil contains several active compounds that are beneficial for the human body such are tocopherol, betacarotene and some types of fatty acids such as oleic acid, linoleic acid, linolenic acid and decanoic. The purpose of this study was to determine the content of secondary metabolites in oil and red fruit juice (Pandanus conoideus). This research method uses qualitative data research methods, namely from the results of analysis of the content of secondary metabolites of oil and Red Fruit juice (Pandanus conoideus) consisting of alkaloids, flavonoids, terpenoids, saponins and tannins, as well as thin-layer chromatography. The results of the study showed that phytochemical screening tests of red fruit oil and red fruit juice hand products gave the same results as red fruit oil (brand x) on the market, that the three samples contained several secondary metabolite compounds namely flavonoids, tannins, and terpenoids